The possibilities of implementing pragmatic instruction with Mental Grounding Techniques in EFL college students context - Al-Obaydi, Liqaa Habeb; Pikhart, Marcel; Namaziandost, Ehsan (Studies in English Language and Education, 2023)
The use of psychological techniques to deal with language problems is a well-known strategy in the process of teaching foreign languages as learners can sometimes suffer from anxiety and stress, so it is essential to help students overcome the psychological barriers they face to cope with the process of learning. This study attempts to deal with pragmatic problems by using a mix of mental grounding techniques and pragmatic activities (awareness-raising activities). The sample of the study comprised participants from Iraq and the Czech Republic. They were first-year college students. The researchers depended on learning zones to determine the suitable time for the experiment (fear zone). The researchers applied self-report surveys in addition to interviews to determine the students with pragmatic problems. Then, at the end of the experiment, the participants were interviewed again to evaluate the experiment in addition to the same self-report survey. Results showed that the two samples responded positively to the mix of techniques used. Moreover, the division of learning zones seems ideal to be dependent in the present study as it specifies the time of challenge the students experienced. The results also clarified that the mix of the two types of activities (pragmatic and grounding activities) demonstrates a kind of remedy that could enhance students level of pragmatics. In the end, no sharp differences were mentioned in the two contexts of the study (Iraq and the Czech Republic); both gained approximate positive results.